Oxford textbook of anaesthesia - Hardman, Jonathan G.; Hopkins, Philip M.; Struys, Michel ([Oxford] : Oxford University Press, 2017)
This resource addresses the fundamental principles of anaesthesia, underpinning sciences and the full spectrum of clinical anaesthetic practice. An international team of experts provide trustworthy, effective, and evidence-based guidance enabling clinicians to provide the very best clinical care to patients.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 7, 2017).
Keywords: Anesthesia